Soil Carbon Storage in Sustainable Land Uses and its Economic Valuation in North Eastern Region of India - Modak, Kingshuk; Mishra, Gaurav; Dutta, Ashis (Indian Forester, 2024)
The conversion of natural forests into large-scale plantations is well recognized in the Northeastern region (NER) of India. But, the potential of these land uses in soil organic carbon (SOC) sequestration and its marketable price for smallholder farmers is less highlighted. Extreme temperature and rainfall can exaggerate carbon (C) emissions from land-use change which can amplify the global climate change. Therefore, the present study was conducted to evaluate the active and passive pools of SOC in the natural forests, coffee, and rubber plantations in Karbi Anglong district of Assam, located in NER of India. To accomplish our objectives, soil samples were collected from 0-30 cm soil layers and pH, bulk density (BD), C pools viz., very labile (CVL ), labile (CL), less labile (CLL), and non-labile (CNL) and total organic C (TOC) were analyzed. The results highlighted that BD, pH, soil organic C pools and stock were significantly influenced by land-use change. The total organic C (TOC) stock in coffee plantations (40.12 t C ha -1) was similar to forest soil (41.61 t C ha-1). The CVL fraction contributed 82% and 64.5% to active C pool (ACP) and TOC, respectively across the land-uses. The active C pool was highest under forest soil (9.44 mg g-1) whereas, the passive C pool was highest under coffee garden (2.88 mg g-1), suggesting its potential in long term SOC sequestration. The estimated marketable soil C price from forest, coffee and rubber were $610.88, $589.07 and $538.43 per ton of CO2 respectively. Thus, our study indicates coffee and rubber plantation can be promoted in fallow jhum lands for their potential to sequester CO2 to mitigate climate change and simultaneously provide financial incentives to smallholder farmers.